Influence of Caloric Vestibular Stimulation on Body Experience in Healthy Humans - Schönherr, Andreas; May, Christian Albrecht (Frontiers in Integrative Neuroscience, 2016)
The vestibular system has more connections with and influence on higher cortical centers than previously thought. These interactions with higher cortical centers and the phenomena that they elicit require a structural intact cerebral cortex. To date, little is known about the role and influence of the vestibular system on one’s body experience. In this study we show that caloric vestibular stimulation (CVS) in healthy participants has an effect on the perceptive component of one’s body experience. After CVS all participants showed a statistically significant difference of thigh width estimation. In contrast to previous studies, which demonstrated an influence of CVS on higher cortical centers with an intact cerebral cortex both the cognitive and affective component of body experience were not effected by the CVS. Our results demonstrate the influence of the vestibular system on body perception and emphasize its role in modulating different perceptive-qualities which contributes to our body experience. We found that CVS has a limited influence on one’s conscious state, thought process and higher cortical functions.